Cloning and Expression of Serotype-2 Simian Betaretrovirus Reverse Transcriptase Gene Isolated from Indonesian Cynomolgus Monkey in Escherichia coli - UUS SAEPULOH; DIAH ISKANDRIATI; FUNGKEY HOETAMA; SELA SEPTIMA MARIYA; DEDY DURYADI SOLIHIN; JOKO PAMUNGKAS; DONDIN SAJUTHI (Indonesian Society for microbiology, 2013)
In this study, we isolated the simian betaretrovirus serotype-2 (SRV-2) reverse transcriptase (RT) gene from infected Indonesian cynomolgus monkey (Macaca fascicularis). The gene was then cloned in Escherichia coli expression system. The SRV-2 RT gene is located between nucleotides 3284-4925 in the polyprotein (Pol) region encodes 547 amino acids. Analysis of expression using SDS-PAGE and western blot techniques showed a specific band of 64.9 kDa, indicating SRV-2 RT recombinant enzyme. Purification of SRV-2 RT recombinant enzyme produced 312 μg mL-1 protein with 7.1 U μL-1 enzyme activities. Application of this recombinant enzyme in reverse transcription-PCR (RT-PCR) of β-globin and β-actin genes produced DNA fragments of 206 and 350 bp, indicating amplification of β-globin and β-actin genes, respectively. Therefore, the expressed SRV-2 RT enzyme was proven to be functional, although the activity was low.